A survey of knowledge, attitudes, and practices on the prevention and control of hand foot and mouth disease among teachers and child care providers in child carecenters, Thailand - คงอยู่, สมคิด; ฮิ้นจ้อย, เสาวพักตร์; สมิตสุวรรณ, พรรณราย; เลิศสุโภชวณิชย์, สมนึก; สุขเกษม, ปรารถนา (Disease Control Journal, 2016)
Hand foot and mouth disease (HFMD) outbreak often occurred in children <5 years old especially in child care centers or kindergartens. Strengthening surveillance program in those risk areas could prevent and control the outbreak of HFMD. The aims of this survey were to explore levels of knowledge, attitudes and practice and to describe any associations among knowledge, attitudes and practice among teachers and child care providers for improvement of HFMD surveillance program. The survey was conducted to cover 287 child care centers under responsible areas of the offices of disease prevention and control in different zones in 10 provinces. A total of 487 teachers and child care providers were sampled by purposive sampling. A face to face interviewing was implemented by using a structured questionnaire. The questionnaire composed three parts of knowledge, attitudes and practices on HFMD that each question was certified by experts and test validity. Results showed that the teachers and child care providers had high levels of HFMD knowledge and practices, but had a moderate level of attitudes scores. In a subgroup analysis, HFMD knowledge in a group of teachers and child care providers in certified child care centers had the highest mean score where as a group of teachers and child care providers in child care centers, which did not join the certification program, had the lowest mean score. There was significantly different in scores of HFMD knowledge among those two groups (p<0.0001 and p = 0.03, accordingly), but no significant difference in scores of attitudes and practices. Knowledge had a positive correlation with attitude (p<0.0001). However, both knowledge and attitudes were not found any correlation with practices. Activities to increase a level of attitude on HFMD needs to be improved because the attitude is a major factor in determining good practices for prevention and control of HFMD among teachers and child care providers. Encouragement of child care centers to raise the standard of good practice under disease-free program could be an important strategy for the prevention and control in a spread of HFMD.